An Autopsy Based Comparative Study Between Males and Females Age of Sagittal Suture fusion at Tertiary Health Care Center at Jaipur (Rajasthan) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: A reasonably correct estimation of age in elderly people is essential in legal, medical, social andadministrative matters. Skulls are usually well preserved in decomposed, mutilated state or in fragmentary bodies.Sagittal suture has a very wide range of fusion. The aim of this study is to collect data of sagittal suture fusion ofmale and female and comparing with each other, so the more appropriate estimation of age can occur by includingsexual dimorphism of sagittal sutural fusion.Material and Methods: This study was conducted in 100 autopsy cases of Department of Forensic Medicine, S.M.S.Medical College & Attached Hospital, Jaipur of aged between 20 to 70 yrs, With making group of male and femalefor each year of age. The obliteration of the sutures was ascertained endocranially as well as ectocranially. TheSagittal suture was studied in four parts and Scale for closure is studied by Acsadi-Nemeskeri complex methodResults: Ectocranially the start of fusion of sagittal suture was observed at the age of 51-60 yrs age group in femalesand in 46-50 yrs in males and endocranially at 31-40 yrs in males and 41-50 yrs in females.Conclusion: When comparison between males and female subjects for ectocranially closure were made, closure wasearlier in males. Completion is perfected at the age of 61-70 years. The study showed that fusion of endocraniumbegan first on S4 & last on S1 in both sexes.Though consensus of opinion in our country is that the obliteration of the skull sutures in females is somewhatearlier than that of males, in the present study no such pattern in difference was noticed in endocrinal suturalfusion.
Keywords: Age, Female, Fusion, Male, Sagittal suture